Managing the demand-supply chain : value innovations for customer satisfaction - Hoover, William E. (John Wiley, 2001)
A proven, innovative approach to meeting customer demand. Combining an intensive focus on customer/marketplace demands with innovative technology tools developed to execute demand chain planning, Managing the Demand-Supply Chain sets forth a powerful new model for fulfilling customer demand in the best possible way. Four of the world's leading demand chain researchers and implementers demonstrate how select high-tech companies, such as Nokia and Dell, have used the demand chain approach to differentiate their value offerings and delight their customers.